Feasibility of Early Vestibular Screening and Developmental Changes in Air- and Bone-Conducted Cervical Vestibular Evoked Myogenic Potentials in Infants and Children with Normal Hearing - Jiali Shen; Xiaobao Ma; Lu Wang; Wei Wang; Jianyong Chen; Qing Zhang; Maoli Duan; Yulian Jin; Jun Yang (Audiology Research)
Objective: To evaluate the feasibility of vestibular screening in infants and investigate age-related changes in the characteristics of air-conducted sound cervical vestibular evoked myogenic potential (ACS-cVEMP) and bone-conducted vibration cervical vestibular evoked myogenic potential (BCV-cVEMP) in infants and children with normal hearing, aiming to provide new insights into the developmental trajectory of vestibular function during early childhood. Methods: A total of 159 subjects aged 3 months to 17 years old were divided into seven age groups. Additionally, 20 adults aged 18–30 years were included as controls to explore developmental changes in the sacculocollic reflex pathway. Results: The response rates of BCV-cVEMP in 3-month-olds were significantly higher than that of ACS-cVEMP (p = 0.048), while no significant difference was observed in other age groups (p > 0.05). Age-related changes were found in both latencies and amplitudes of ACS-cVEMP and BCV-cVEMP. ACS-cVEMP latencies reached adult levels at 13–17 years, while BCV-cVEMP latencies normalized by 7–12 years. ACS-cVEMP amplitudes increased with age, stabilizing at 4 years, whereas BCV-cVEMP amplitudes peaked at 4–6 years before gradually decreasing. Conclusions: This study demonstrates that cVEMP is not only a viable tool for vestibular screening in infants but also reveals crucial age-related developmental changes in the vestibular system. These findings contribute new insights into the maturation of the vestibular reflex pathways and provide normative data that can be used to guide early vestibular screening practices.